Необхідність розроблення методичних рекомендацій з організації та проведення огляду громадської безпеки та цивільного захисту Міністерством внутрішніх справ України: кримінологічні та нормативно-безпекові аспекти - Гладкова, Є. О.; Gladkova, Ye. O.; Безпалько, С. В.; Bezpalko, S. V.; Пахнін, М. Л.; Pakhnin, M. L.; Кріцак, І. В.; Kritsak, I. V.; Денищук, Д. Є.; Denyshchuk, D. Ye.; Іван Кріцак; Денис Денищук; et al. (Юридичний науковий електронний журнал. - 2022. - № 10. - С. 541-545, 2022)
Розглянуто актуальні питання громадської безпеки та цивільного захисту з метою подальшого розроблення методичних рекомендацій з організації та проведення огляду, що проводиться Міністерством внутрішніх справ України. Здійснена спроба вироблення стратегій і тактик громадської безпеки та цивільного захисту з наданням авторських пропозицій та рекомендацій. Наголошується, що громадський (публічний) порядок та безпека в умовах нинішньої російсько-української війни можуть розглядатися у взаємодії як рівнозначні категорії за суспільною значущістю з Національною безпекою держави. Акцентовано увагу на глобальних, регіональних та національних аспектах безпекових питань, з визначенням цілей пріоритетів та завдань державної політики у правоохоронній сфері, а також моделей відповідного втручання і реагування на суспільно шкідливі та небезпечні виклики і загрози.

The article deals with topical issues public safety and civil protection for the purpose of further development methodical recommendations on organization and implementation review conducted by the Ministry of Internal Affairs of Ukraine. An attempt was made to develop strategies and tactics public safety and civil protection with the provision of author’s suggestions and recommendations. It is emphasized that public (public) order and security in the conditions of the current russian-ukrainian war can be considered in interaction as equivalent categories in terms of social significance with the National Security of the state. Public order is proposed to be analyzed as a kind of rear and protection in effective organization of national security (without a reliable rear, there can be no victory). A significant role in these processes belongs to such state and public institutions as Armed Forces of Ukraine, volunteers, doctors and the church, the level of trust in which, according to the corresponding hierarchy, is currently the highest in the state, which serves as an example for all ‒ as in the most difficult time for the country should help those, who needs it. It is emphasized that safety in the current conditions has a cross-border nature, where cyber security and scientometric monitoring are called to take a leading place in development of strategic policies of the state (criminological, criminal-legal, economic, social, and many others). For this, scientific and innovative centers should be created in many branches and spheres of human knowledge, with the involvement of the best specialists in research work, capable in the shortest possible time collect, analyze (process) the most diverse types of information, with the development of proposals in the relevant regulatory and methodological recommendations and further management decisions. Emphasis is placed on global, regional and national aspects security issues, with determining the goals, priorities and tasks of state policy in law enforcement, as well as models of appropriate intervention and response to socially harmful and dangerous challenges and threats. A Canadian model is offered SARO (scanning, analysis, response, assessment) and and the famous method of SWOT analysis, which widely used in strategic planning, where: (Strengths) – strengths; (Weaknesses) – weaknesses; (Opportunities) – opportunities arising from the existing situation; (Threats) – threats that can be realized.

Рассмотрены актуальные вопросы общественной безопасности и гражданской защиты для дальнейшей разработки методических рекомендаций по организации и проведению осмотра, проводимого Министерством внутренних дел Украины. Предпринята попытка выработки стратегий и тактик общественной безопасности и гражданской защиты с предоставлением авторских предложений и рекомендаций. Отмечается, что общественный (публичный) порядок и безопасность в условиях нынешней российско-украинской войны могут рассматриваться во взаимодействии как равнозначные категории по общественной значимости с национальной безопасностью государства. Акцентировано внимание на глобальных, региональных и национальных аспектах вопросов безопасности, с определением целей приоритетов и задач государственной политики в правоохранительной сфере, а также моделей соответствующего вмешательства и реагирования на общественно вредные и опасные вызовы и угрозы.
The need to develop methodological recommendations on the organization and conduct of the review public security and civil defense by the Ministry of Internal Affairs of Ukraine: criminology and regulatory and security aspects
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Міністерство внутрішніх справ України; Ministry of Internal Affairs of Ukraine; Министерство внутренних дел Украины; методичні рекомендації; methodological recommendations; методические рекомендации; громадська безпека; public security; общественная безопасность; національна безпека; national security; национальная безопасность; цивільний захист; civil protection; гражданская защита; російсько-українська війна; Russian-Ukrainian war; русско-украинская война